Hot press-formed body

CN117836461BActive Publication Date: 2026-10-23NIPPON STEEL CORPORATION
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202280057304.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-10-12
Filing Date
2022-09-22
Publication Date
2026-10-23
Estimated Expiration
2042-09-22

AI Technical Summary

Benefits of technology

[0042]根据本发明,能够提供涂装后耐蚀性优异的热冲压成形体。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004709770870000151
    Figure BDA0004709770870000151
  • Figure BDA0004709770870000161
    Figure BDA0004709770870000161
  • Figure BDA0004709770870000171
    Figure BDA0004709770870000171
Patent Text Reader

Abstract

The present application provides a hot press forming body, which has a steel material and a plated layer, the chemical composition of the plated layer contains, in mass%, Al: 0-70%, Fe: 10-60%, Si: 0-20%, C group elements: any one or two of Li, Y and the total content is 0.00001-0.3%, sometimes further contains one or more than two of Sb, Pb, B, Cu, Ti, Cr, Nb, Ni, Mn, Mo, Ag, Co, Sn and Bi, the remaining part contains Zn and impurities; the plated layer contains η-Zn phase or Zn-containing phase.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to hot-stamped formed articles. This application claims priority based on Japanese Patent Application No. 2021-167251, filed on October 12, 2021, the contents of which are incorporated herein by reference. Background Technology

[0002] Hot stamping (hot forming) is a known technique for forming materials that are difficult to shape, such as high-strength steel sheets. Hot stamping is a thermoforming technique in which the material to be formed is heated before forming. In this technique, because the material is heated before forming, the steel has good formability during forming due to its softness. Therefore, even high-strength steel can be formed into complex shapes with high precision. Furthermore, since the steel is quenched simultaneously with forming using a pressure forming die, the formed steel has sufficient strength.

[0003] For example, Patent Document 1 describes a steel sheet for hot stamping forming, which is coated with a metal containing 2.0 to 24.0 wt% zinc, 7.1 to 12.0 wt% silicon, 1.1 to 8.0 wt% magnesium (arbitrarily selected element), less than 0.3 wt% Pb, Ni, Zr or Hf (arbitrarily selected element), the remainder containing aluminum and impurities, and an Al / Zn ratio exceeding 2.9.

[0004] Furthermore, Patent Document 2 describes a method for obtaining a component as a manufacturing method for a hot-stamped formed body. This method involves heating a steel sheet to 840–950°C for hot forming and then cooling it to obtain a component having a steel containing martensite. The steel sheet is coated with a metal containing 2.0–24.0 wt% zinc, 7.1–12.0 wt% silicon, 1.1–8.0 wt% magnesium (an optional element), and less than 0.3 wt% of Pb, Ni, Zr, or Hf (an optional element), with the remainder containing aluminum and impurities, and an Al / Zn ratio exceeding 2.9.

[0005] Existing technical documents

[0006] Patent documents

[0007] Patent Document 1: International Publication No. 2017 / 017513

[0008] Patent Document 2: International Publication No. 2017 / 017514 Summary of the Invention

[0009] The problem that the invention aims to solve

[0010] However, in Patent Documents 1 and 2, when the steel sheet is heated for hot stamping, the Zn contained in the metal plating (coating) of the steel sheet evaporates. As a result, the sacrificial anode corrosion resistance of the hot-stamped product decreases, thereby reducing its resistance to red rust. Consequently, there are problems with reduced corrosion resistance and coating adhesion after coating.

[0011] The present invention was made in view of the above circumstances, and its object is to provide a hot stamped form with excellent corrosion resistance and coating adhesion after coating.

[0012] Methods for solving problems

[0013] To address the aforementioned issues, the present invention employs the following configuration.

[0014] [1] A hot-stamped formed body comprising steel and a coating, characterized in that...

[0015] The chemical composition of the coating, expressed in % by mass, contains

[0016] Al: 0-70%

[0017] Fe: 10-60%

[0018] Si: 0-20%, and

[0019] Group C elements: any one or two of Li and Y, with a combined content of 0.00001–0.3%, and further containing a combined content of 0–5%.

[0020] Sb: 0-0.5%

[0021] Pb: 0-0.5%

[0022] B: 0-0.5%

[0023] Cu: 0–1.0%

[0024] Ti: 0-1.0%

[0025] Cr: 0–1.0%

[0026] Nb: 0–1.0%

[0027] Ni: 0-1.0%

[0028] Mn: 0~1.0%

[0029] Mo: 0–1.0%

[0030] Ag: 0-1.0%

[0031] Co: 0-1.0%

[0032] Sn: 0–1.0%, and

[0033] Bi: any one or more of the following: 0% to 1.0%

[0034] The remaining portion contains Zn and impurities;

[0035] The coating contains an η-Zn phase or a Zn-containing phase.

[0036] [2] According to the hot stamping formed body described in [1] above, wherein the chemical composition of the coating contains one or two elements from group A and group B.

[0037] Group A elements: 0.0010–15% Mg, and any one or two selected from Ca or Sr, with a combined content of 0.0001% or more but less than 5.5%.

[0038] Group B elements: selected from one or more of Zr, La, and Ce, with a total content of 0.0001 to 0.5%.

[0039] [3] According to the hot stamping formed body described in [1] or [2] above, the total amount of the C group elements is 0.001 to 0.3%.

[0040] [4] The hot stamping formed body according to any one of [1] to [3] above, wherein the Mg content in the A group of elements is 1 to 15%.

[0041] Invention Effects

[0042] According to the present invention, a hot stamped part with excellent corrosion resistance after coating can be provided. Detailed Implementation

[0043] The inventors have conducted in-depth research on a method to prevent the evaporation of Zn from the coating of a heated coated steel sheet during hot stamping. The coating contains specific elements within a defined range, and a coated steel sheet whose surface has been oxidized with water vapor is used as the blank during coating formation. As a result, the inventors discovered that by suppressing the evaporation of Zn from the coated steel sheet during hot stamping, Zn can remain in the coating.

[0044] Furthermore, if the coated steel sheet is heated during hot stamping, the substrate of the steel sheet reacts with the constituent elements of the coating to form an alloy layer. However, by pre-containing specific elements within a prescribed range in the coating, the alloy layer can be modified. Thus, the inventors discovered that coating expansion becomes less likely to occur when evaluating post-coating corrosion resistance, thereby further improving the post-coating corrosion resistance and coating adhesion of the hot-stamped body.

[0045] The following describes a hot-stamped formed article with excellent corrosion resistance and coating adhesion after coating, a method for manufacturing the hot-stamped formed article, and a method for manufacturing a coated steel sheet for hot stamping, according to embodiments of the present invention.

[0046] First, the raw material for the hot-stamped formed body of this embodiment, namely the galvanized steel sheet for hot stamping, and its manufacturing method will be explained.

[0047] Coated steel sheet for hot stamping comprises a steel sheet and a coating formed on the surface of the steel sheet. The coating may be formed on one side or both sides of the steel sheet.

[0048] There are no particular restrictions on the type of steel plate. It can be determined according to the applicable product or the required strength and plate thickness. For example, hot-rolled steel plates as described in JIS G3193:2008 or cold-rolled steel plates as described in JIS G3141:2017 can be used.

[0049] Furthermore, there are no particular limitations on the steel plate; steel plates with a chemical composition containing C: 0.1–0.5%, Si: 0.001–3%, Mn: 0.3–3%, Al: 0.0002–2%, and the remainder including Fe and impurities can be used. Moreover, in the description of the chemical composition of the steel plate, "%" refers to "mass %".

[0050] The coating has a chemical composition containing Al: 0–70%, Fe: 0–15%, Si: 0–20%, and elements from group C, with the remainder being Zn and impurities. The reasons for these elemental limitations are explained below regarding the chemical composition of the coating. Furthermore, in the description of the coating's chemical composition, "%" refers to "mass %".

[0051] Al: 0-70%

[0052] Al is an element that improves the barrier properties of the coating on hot-stamped coated steel sheets and can be included as needed. Furthermore, Al forms an alloy layer during hot stamping by reacting with the substrate of the steel sheet. The lower limit of the Al content is set to 0% or more. The upper limit of the Al content is set to 70% or less. If the Al content exceeds 70%, the Zn content decreases relatively, thus preventing Zn from remaining in the coating after hot stamping. This reduces the sacrificial anode corrosion resistance of the coating, thereby decreasing the corrosion resistance of the hot-stamped body after coating, which is undesirable. The lower limit of the Al content can also be set to 20% or more or 30% or more. The upper limit of the Al content can also be set to 65% or less or 60% or less.

[0053] Fe: 0-15%

[0054] Fe can also be included in the coating of hot-stamped coated steel sheets. During hot-dip galvanizing, Fe sometimes diffuses into the coating from the steel sheet. Some of the Fe alloys with Al and other alloys in the coating. Furthermore, even during hot stamping, Fe diffuses from the steel sheet into the coating and combines with Al and other alloys in the coating to form an alloy layer. The Fe content is set to 0% or more. Furthermore, the Fe content is set to 15% or less. If the Fe content exceeds 15%, the Fe content in the coating after hot stamping is excessive, which easily leads to red rust and is therefore undesirable. The lower limit of the Fe content in the coating of hot-stamped coated steel sheets can also be set to 1% or more or 2% or more. Furthermore, the upper limit of the Fe content can also be set to 5% or less or 4% or less.

[0055] Si: 0-20%

[0056] Si is an element that, when forming a coating on a steel sheet using a hot-dip galvanizing method, improves the adhesion between the steel sheet and the coating by suppressing excessive thickening of the alloy layer formed between the steel sheet and the coating. Therefore, it may be included in the coating. Furthermore, Si, when included with Mg, forms compounds with Mg, which helps improve corrosion resistance after coating. The lower limit of the Si content is set to 0% or more. Alternatively, the lower limit of the Si content may be set to 1% or more or 2% or more. On the other hand, if the Si content exceeds 20%, the processability of the coating decreases, and there are concerns about cracking and other issues in the coating after hot stamping. Therefore, the Si content is set to 20% or less. The upper limit of the Si content may also be set to 10% or less, and more preferably 5% or less.

[0057] In addition, the coating may contain elements from group C. These elements are more easily oxidized than Al, Fe, Si, and Zn, and readily form oxides in the coating during hot stamping. It can be inferred that by pre-containing these elements in the coating, the oxides of these elements during hot stamping can suppress the evaporation of Zn from the heated coating.

[0058] Group C elements (selected from any one or two of Li and Y, totaling 0.00001 to 0.3%)

[0059] By including elements from group C, the evaporation of Zn during hot stamping can also be suppressed. The total content of group C elements is set to 0.00001 to 0.3%. The total content of group C elements is further preferably 0.001 to 0.3%. The total content of group C elements can also be set to 0.001% or more, or 0.01% or more, or 0.2% or less, or 0.1% or less. If the total content of group C elements is below the lower limit, the effect of suppressing Zn evaporation is not sufficient. Furthermore, if the total content of group C elements exceeds the upper limit, the coating after hot stamping will undergo excessive oxidation, resulting in a decrease in corrosion resistance and coating adhesion after coating.

[0060] In addition, the coating may also contain one or two of the elements from group A and group B listed below. These elements, like those from group C, are more easily oxidized than Al, Fe, Si, and Zn, and tend to form oxides in the coating during hot stamping.

[0061] Group A elements (0.0010–15% Mg, and any one or two of the following: 0.0001% or more but less than 5.5% Ca or Sr)

[0062] When group A elements are included, Mg and one or two elements selected from Ca or Sr are contained. That is, the combination of elements when group A elements are included is Mg and Ca, Mg and Sr, or Mg, Ca, and Sr. This suppresses Zn evaporation during hot stamping. Furthermore, excellent coating adhesion is obtained. Preferably, the Mg content is set to 0.0010–15%, more preferably 1–15%. The Mg content can also be set to 1% or more, or 3% or more, or 14% or less, or 10% or less. Furthermore, it is preferable that the total amount of one or two elements selected from Ca or Sr is set to 0.0001% or more and less than 5.5%. The total amount of Ca and Sr can also be set to 0.0002% or more, or 0.01% or more, or 5% or less, or 4% or less. If the content of each element is below the lower limit, the effect of suppressing Zn evaporation is insufficient. Furthermore, if the content of each element exceeds the upper limit, the coating after hot stamping will undergo excessive oxidation, resulting in a decrease in corrosion resistance after coating.

[0063] Group B elements (any one or more of Zr, La, and Ce, totaling 0.0001% to 0.5%)

[0064] By including elements from group B, the evaporation of Zn during hot stamping can be suppressed. Furthermore, excellent coating adhesion can be obtained. It is preferable to set the total content of group B elements to 0.0001% to 0.5%. Alternatively, the total content of group B elements can be set to 0.0002% or more, or 0.01% or more, or 0.4% or less, or 0.3% or less. If the total content of group B elements is below the lower limit, the effect of suppressing Zn evaporation is insufficient. Furthermore, if the total content of group B elements exceeds the upper limit, excessive oxidation occurs in the coating after hot stamping, resulting in decreased corrosion resistance after coating.

[0065] In addition, in the coating of this embodiment, a portion of Zn may be substituted, and the coating may contain any one or more of the following elements in a total range of 0-5%: Sb: 0-0.5%, Pb: 0-0.5%, B: 0-0.5%, Cu: 0-1.0%, Ti: 0-1.0%, Cr: 0-1.0%, Nb: 0-1.0%, Ni: 0-1.0%, Mn: 0-1.0%, Mo: 0-1.0%, Ag: 0-1.0%, Co: 0-1.0%, Sn: 0-1.0%, and Bi: 0-1.0%. If the total amount of these elements exceeds 5%, the viscosity of the coating bath increases, and the preparation of the coating bath itself becomes difficult, making it impossible to produce coated steel sheets with good coating properties.

[0066] Sb, Pb, and B are elements that can be added to the coating. By including these elements in the coating, the corrosion resistance of the planar portion of the coating is improved before and after hot stamping. The corrosion resistance of the planar portion refers to the corrosion resistance of the coated surface. A significant improvement in corrosion resistance can be observed by including 0.001% or more, preferably 0.01% or more or 0.1% or more; therefore, it is preferable to include these elements at 0.001% or more respectively. As long as these elements are included in the range of 0.5% or less, the viscosity of the coating bath will not increase, allowing for the preparation of the coating bath and thus enabling the manufacture of coated steel sheets with good coating properties.

[0067] Cu, Ti, Cr, Nb, Ni, Mn, Mo, Ag, and Co are metallic elements that can be arbitrarily included in the coating. Including these elements can improve the corrosion resistance of the planar portion of the coating before and after hot stamping. Significant improvements in corrosion resistance can be observed with amounts of 0.0001% or more, 0.001% or more, or 0.10% or more; therefore, it is preferable to include these elements at 0.0001% or more. As long as these elements are included in the range of 1.0% or less, the viscosity of the plating bath will not increase, allowing for the preparation of the plating bath and the production of coated steel sheets with good coating properties.

[0068] Sn and Bi are elements that can be included arbitrarily. The presence of Sn and Bi improves the sacrificial anode corrosion resistance of the coating before and after hot stamping. The improvement in sacrificial anode corrosion resistance can be confirmed by including amounts of 0.001% or more and 0.01% or more, respectively. However, excessive Sn and Bi content, while increasing the sacrificial anode corrosion resistance of the coating, results in the coating becoming more susceptible to dissolution, negatively impacting the corrosion resistance of planar surfaces, etc. Furthermore, the appearance of the coating is prone to change. Therefore, the content of Sn and Bi is set to 1.0% or less, respectively.

[0069] The remaining portion of the chemical composition of the coating includes Zn and impurities. Zn can improve the sacrificial anode corrosion resistance of the coated steel sheet for hot stamping. Furthermore, Zn remains in the coating after hot stamping, forming an η-Zn phase or a Zn-containing phase in the coating of the hot-stamped body. This improves the corrosion resistance of the hot-stamped body after coating. Therefore, Zn is contained as a remaining portion. The content of Zn is not particularly limited as long as it is contained as a remaining portion, but the Zn content can be 5% or more, more preferably 8% or more.

[0070] Impurities refer to components contained in raw materials or mixed in during the manufacturing process; they are components that are not intentionally present. For example, sometimes trace amounts of impurities are introduced into the coating through atomic diffusion between the steel plate (substrate) and the plating bath.

[0071] Furthermore, the surface of the coating of the hot-stamping coated steel sheet in this embodiment is subjected to water vapor oxidation treatment.

[0072] The preferred coating thickness for hot-stamped coated steel sheets is 20–160 g / m². 2 Within the range.

[0073] Next, the manufacturing method of galvanized steel sheet for hot stamping will be described. The manufacturing method of galvanized steel sheet for hot stamping consists of a hot-dip galvanizing process and an exposure process.

[0074] In the hot-dip galvanizing process, molten metal constituting the plating bath is deposited on the surface of a steel sheet by immersing it in a hot-dip galvanizing bath with a specified chemical composition and then lifting it out. The composition of the hot-dip galvanizing bath is roughly the same as the composition of the coating to be formed, so it only needs to be adjusted according to the desired chemical composition of the coating. For example, the composition of the plating bath may, by mass percent, contain Al: 0–70%, Fe: 0–15%, Si: 0–20%, and elements from group C, and further contain a total of 0–5% of any one or more of the following: Sb: 0–0.5%, Pb: 0–0.5%, B: 0–0.5%, Cu: 0–1.0%, Ti: 0–1.0%, Cr: 0–1.0%, Nb: 0–1.0%, Ni: 0–1.0%, Mn: 0–1.0%, Mo: 0–1.0%, Ag: 0–1.0%, Co: 0–1.0%, Sn: 0–1.0%, and Bi: 0–1.0%, with the remainder containing Zn and impurities. Alternatively, the plating bath may further contain one or two of the aforementioned elements from groups A and B.

[0075] Alternatively, the steel sheet can be reduced annealed before the hot-dip galvanizing process. Annealing conditions can be well-known, such as heating to 750–900°C in a 5% H2-N2 atmosphere with a dew point above -10°C, and then holding for 30–240 seconds.

[0076] Ideally, the coating adhesion should be adjusted immediately after the steel plate is lifted from the plating bath by gas friction contact based on N2 gas.

[0077] Next, in the exposure process, the coating, which is cooling after the hot-dip plating process, is exposed to an N2 atmosphere containing H2O and with a dew point of 0°C or higher for 3 to 300 seconds. The exposure is carried out within a temperature range of 700 to 460°C. This exposure process causes water vapor oxidation on the coating surface. In particular, it is presumed that elements of group A, group B, and group C contained in the coating will preferentially oxidize during the exposure process. Preferably, the average cooling rate during the temperature range of 700 to 460°C is set to a range of 5 to 60°C / second.

[0078] The exposure process is performed while the coating is within a temperature range of 700–460°C. If exposure is performed at a relatively high temperature (above 700°C), the coating will be excessively oxidized. Conversely, if exposure is performed at a relatively low temperature (below 460°C), water vapor oxidation of the coating surface cannot occur, and Zn evaporation cannot be suppressed during hot stamping.

[0079] Furthermore, the atmosphere for the exposure process is set to an N2 atmosphere containing H2O and with a dew point above 0°C. If oxygen is present in the atmosphere, oxygen oxidation takes precedence over water vapor oxidation, resulting in the inability to suppress Zn evaporation during hot stamping. Therefore, the oxygen content in the atmosphere is set to be below the impurity level.

[0080] Furthermore, the dew point of the N2 atmosphere containing H2O is preferably above 0°C. If the dew point is below 0°C, water vapor oxidation on the coating surface will not proceed sufficiently, and Zn evaporation cannot be suppressed during hot stamping. A higher dew point is more favorable for water vapor oxidation, so there is no need to specifically limit the upper limit of the dew point.

[0081] The exposure time is set to 3–300 seconds. If the exposure time is less than 3 seconds, the water vapor oxidation on the coating surface will not proceed sufficiently, and Zn evaporation cannot be suppressed during hot stamping. On the other hand, since the effect reaches saturation even if the exposure time exceeds 300 seconds, it is sufficient to set the exposure time to less than 300 seconds.

[0082] In this way, the hot-stamped steel sheet of this embodiment is manufactured.

[0083] Next, the hot stamping formed article and the manufacturing method of the hot stamping formed article according to this embodiment will be described.

[0084] A hot-stamped formed body comprises steel and a coating formed on the surface of the steel. The coating may be formed on one side or both sides of the steel.

[0085] There are no particular restrictions on the type of steel. The choice depends on the intended product, required strength, and plate thickness. For example, hot-rolled steel sheets as described in JIS G3193:2008 or cold-rolled steel sheets as described in JIS G3141:2017 can be used. The steel's microstructure is enhanced by rapid cooling from a high temperature during the hot stamping process, resulting in a higher proportion of martensite.

[0086] In addition, steel with a chemical composition including C: 0.1-0.5%, Si: 0.001-3%, Mn: 0.3-3%, Al: 0.0002-2%, and the remainder including Fe and impurities can also be used as steel. Furthermore, in the description of the chemical composition of steel plates, "%" refers to "mass %".

[0087] The coating has a chemical composition containing Al: 0–70%, Fe: 10–60%, Si: 0–20%, and elements from group C, with the remainder being Zn and impurities. Furthermore, it may also contain one or two elements from group A and group B. The reasons for limiting the chemical composition of the coating are explained below. However, the reasons for limiting the elements from group A, Si, and C, as well as for limiting elements such as Sb and Pb that are included to replace a portion of Zn, are the same as those explained for coated steel sheets for hot stamping. Therefore, the reasons for limiting Fe are explained below.

[0088] Fe: 10-60%

[0089] Fe is contained in the coating of hot-stamped coated steel sheet in the range of 0-15%. Furthermore, by hot-stamping the hot-stamped coated steel sheet, Fe further diffuses from the steel sheet into the coating, resulting in a Fe content of 10% or more in the hot-stamped coating. The Fe diffused through hot stamping, together with the originally contained Fe, combines with Al or Zn contained in the coating to form an alloy layer. By forming an alloy layer, the corrosion resistance of the hot-stamped body after coating can be improved, as described later. On the other hand, if the Fe content exceeds 60%, the resistance of the hot-stamped body to red rust decreases, and consequently, the corrosion resistance after coating decreases, which is therefore undesirable. The lower limit of the Fe content can also be set to 15% or more or 20% or more. Furthermore, the upper limit of the Fe content can also be set to 50% or less or 40% or less.

[0090] Remaining components: Zn and impurities

[0091] The remaining portion contains Zn and impurities. Impurities refer to components present in the raw materials or introduced during the manufacturing process; they are components not intentionally present in the coated steel sheet. Furthermore, there are no particular restrictions on the Zn content, but it can be 5% or more, more preferably 8% or more.

[0092] The coating of the hot-stamped formed body contains an η-Zn phase or a Zn-containing phase. For example, the ZnO phase can be cited as a Zn-containing phase. Furthermore, especially when containing group A elements, Zn sometimes exists as an intermetallic compound with group A elements, such as MgZn2 phase, Mg2Zn3 phase, MgZn phase, or CaZn. 11 Phase, CaZn 13 Phase, SrZn 11 Related to SrZn 13The phase is contained within the coating. The chemical processability of the coating is improved when the ZnO phase or an intermetallic compound phase of Zn with group A elements is present. The η-Zn phase or Zn-containing phase is located on the surface side of the coating, approximately half the thickness of the coating. Furthermore, the η-Zn phase or Zn-containing phase is distributed in the grain boundaries of the alloy layer, as described later. By containing the η-Zn phase or Zn-containing phase, sacrificial anodic corrosion resistance can be imparted to the coating of hot-stamped bodies, thereby improving post-coating corrosion resistance. In addition, resistance to red rust is also improved.

[0093] The presence of the η-Zn phase or Zn-containing phase can be confirmed by X-ray diffraction (XRD) analysis of the coated surface of the hot-stamped body. Specifically, a Cu tube is used as the XRD source to perform XRD analysis on the coated surface. The presence of a peak at a 2θ angle of 42.9–43.6° indicates the presence of the η-Zn phase. Furthermore, for other Zn-containing phases, the presence of a peak within ±0.3° of the peak with the highest intensity reflection in the ICDD chart indicates the presence of that Zn-containing phase in the coating.

[0094] Regarding the remaining microstructure of the coating on the hot-stamped body, when the coating contains Al, Fe in the coating alloys with Al to form an Fe-Al alloy layer. The grain boundaries of the grains forming the alloy layer contain the aforementioned η-Zn phase or Zn-containing phase. Furthermore, as mentioned above, intermetallic compounds of Zn with group A elements are sometimes also distributed on the surface layer of the coating (the upper side of the 1 / 2t portion). t refers to the coating thickness. The Al content of the coating can also be 0%, and when the Fe-Al alloy layer is absent, Fe alloys with Zn, and the η-Zn phase exists on the Fe-Zn alloy layer.

[0095] The preferred coating thickness of the hot-stamped body is 20–160 g / m². 2 Within the range.

[0096] The chemical composition of the coating of hot-stamped steel sheets and hot-stamped bodies can be determined by the following methods.

[0097] First, the coating is peeled off and dissolved using an acid containing a corrosion inhibitor that suppresses corrosion of the substrate (steel) to obtain an acid solution. Then, the chemical composition of the coating is obtained by determining the acid solution using ICP analysis. There are no particular restrictions on the type of acid, as long as it can dissolve the coating. The chemical composition is determined as an average chemical composition.

[0098] In ICP analysis, since O cannot be analyzed, the above chemical composition does not take into account the elemental content of O present in the coating.

[0099] Next, the manufacturing method of the hot stamping formed body of this embodiment will be described.

[0100] The hot-stamped coated steel sheet described above is cut into a specified shape as a blank. Next, the blank is heated to a holding temperature of 850°C or higher, and the holding time at the holding temperature is set to 200 seconds or less. Then, while forming the heated blank into the desired shape using a die, it is quenched inside the die.

[0101] There is a concern that Zn might evaporate from the coating of the hot-stamped steel sheet due to the holding temperature exceeding 850°C. However, since the coating of the hot-stamped steel sheet contains elements from group C, Zn evaporation can be suppressed. Furthermore, by including elements from group C in the coating, an n-Zn phase or a Zn-containing phase can be included in the coating. In this way, the hot-stamped formed body of this embodiment is manufactured.

[0102] As explained above, the manufacturing method of the hot-stamped coated steel sheet according to this embodiment can produce a blank for hot-stamped forming bodies with excellent corrosion resistance and coating adhesion after coating. Furthermore, the hot-stamped forming body according to this embodiment can further improve corrosion resistance and coating adhesion after coating compared to previous methods.

[0103] Example

[0104] The embodiments of the present invention will be described below.

[0105] As the steel sheet to be coated, a cold-rolled steel sheet with a thickness of 1.6 mm (0.2% C-1.3% Mn) is prepared.

[0106] After the steel plate was cut into 100mm × 200mm pieces, reduction annealing and hot-dip galvanizing were continued using an intermittent hot-dip galvanizing test device. The plate temperature was measured using a thermocouple spot-welded to the center of the original plate.

[0107] During reduction annealing, the annealing is carried out in a furnace with an oxygen concentration of less than 20 ppm, in a gas atmosphere containing 5% H2 and the remainder containing N2, at 800°C for 120 seconds.

[0108] After reduction annealing, the steel sheet is air-cooled with N2 gas. When the steel sheet temperature reaches the bath temperature +20°C, it is immersed in the plating bath for about 3 seconds. Then, it is lifted at a lifting speed of 20-200 mm / s.

[0109] The plating bath composition, by mass%, contains Al: 0–70%, Fe: 0–15%, Si: 0–20%, and the aforementioned Group C elements, further containing a total of 0–5% of any one or more of the following: Sb: 0–0.5%, Pb: 0–0.5%, B: 0–0.5%, Cu: 0–1.0%, Ti: 0–1.0%, Cr: 0–1.0%, Nb: 0–1.0%, Ni: 0–1.0%, Mn: 0–1.0%, Mo: 0–1.0%, Ag: 0–1.0%, Co: 0–1.0%, Sn: 0–1.0%, and Bi: 0–1.0%. The remainder contains Zn and impurities. Additionally, it contains one or two of the aforementioned Group A and Group B elements.

[0110] Of these, Nos. 1–33, 52–56, and 67–76 do not contain elements of group C. Furthermore, Nos. 77–79 have group C element content that deviates from the preferred range. Additionally, Nos. 80–87 did not undergo an exposure process.

[0111] The substrate with the coating formed was cooled after adjusting the coating adhesion using N2 friction contact gas. Then, as an exposure process, during the cooling after hot-dip plating, the coating was exposed to the atmospheres described in Tables 1B, 1D, and 1F while the coating was in a temperature range of 700–460°C. The exposure time was set to a range of 3–300 seconds. Furthermore, in Tables 1B, 1D, and 1F, "N2 (dew point x°C)" refers to an N2 atmosphere containing H2O with a dew point of x°C. The average cooling rate during the temperature range of 700–460°C was set to a range of 5–60°C / second.

[0112] Next, the obtained coated steel sheet is heated to 900°C in a muffle furnace with an atmospheric atmosphere, held at 900°C for 100 seconds, and then taken out and subjected to hot stamping with a flat die for pressure forming and rapid cooling, thereby obtaining a hot stamped body.

[0113] The presence or absence of the η-Zn phase or Zn-containing phase in the coating was determined using the method described above for the obtained hot-stamped formed body. The results are shown in Tables 1A to 1F. Furthermore, the composition of the coating of the hot-stamped formed body is also shown in Tables 1A to 1F.

[0114] The composition of the coating can be determined by immersing a 30mm × 30mm sample in a 10% HCl aqueous solution containing a corrosion inhibitor, and then peeling off the coating by acid washing, followed by ICP analysis of the elements dissolved in the aqueous solution.

[0115] In addition, the corrosion resistance of the hot-stamped body was evaluated after coating.

[0116] Specifically, a 50×100mm sample was taken from the hot-stamped body, treated with Zn phosphoric acid (SD5350 system: standard manufactured by Paint Industrial Coding Co., Ltd., Japan), and then electrophoretic coating (PN110 POWERNICS (registered trademark) Gray: standard manufactured by Paint Industrial Coding Co., Ltd., Japan) was performed to achieve a thickness of 20μm. After baking at a baking temperature of 150°C for 20 minutes, a cut was made in the center of the sample to reach the substrate.

[0117] Then, a composite cyclic corrosion test was conducted according to JASO (M609-91) to determine the number of cycles in which red rust appeared from the cut part. Cases with more than 120 cycles of red rust appearance were designated as "AA", cases with 60-120 cycles as "A", and cases with less than 60 cycles as "B". AA and A were set as acceptable, and B was set as unacceptable.

[0118] In addition, the coating adhesion of the hot-stamped body was evaluated.

[0119] After undergoing the same treatment as for post-coating corrosion resistance, the samples were immersed in a 5% sodium chloride aqueous solution at 55°C for 10 days. Then, the samples were removed, and Nichiban tape (model: CT405A-24) was applied to the cut surface and immediately peeled off. Coating adhesion was evaluated based on the length of the peeled portion originating from the cut, i.e., the coating peel width. Cases with a peel width less than 1.5 mm were designated as "AA", cases with a peel width between 1.5 mm and 2 mm were designated as "A", and cases with a peel width of 2 mm or more were designated as "B". AA and A were set as acceptable, and B was set as unacceptable.

[0120] As shown in Tables 1A to 1F, hot-stamped bodies (No. 1–33, No. 52–56) with coatings excluding Group C elements exhibit excellent corrosion resistance after coating, but poor coating adhesion. Conversely, hot-stamped bodies (No. 34–51, No. 57–66) with coatings containing Group C elements demonstrate excellent corrosion resistance and coating adhesion after coating. In particular, hot-stamped bodies with a Mg content of 1% or more, or a total Group C element content of 0.001–0.3%, exhibit even better corrosion resistance after coating. Furthermore, hot-stamped bodies (No. 57–66) containing one or two of Group A and Group B elements exhibit even better corrosion resistance after coating. In Tables 1E and 1F, hot-stamped bodies with coatings containing no C-group elements (Nos. 67-76), hot-stamped bodies with coatings containing C-group elements outside the preferred range (Nos. 77-79), and hot-stamped bodies without an exposure process and outside the manufacturing conditions range (Nos. 80-87) all exhibit poor corrosion resistance and coating adhesion after coating. Furthermore, the hot-stamped body with Y-group elements vapor-deposited on the coating (No. 87) also exhibits poor corrosion resistance after coating because it lacks an exposure process and is outside the manufacturing conditions range.

[0121]

[0122]

[0123]

[0124]

[0125]

[0126]

Claims

1. A hot-stamped formed body comprising steel and a coating, characterized in that, The chemical composition of the coating, expressed in % by mass, contains Al:0~70%、 Fe: 10-60%, Si: 5-20%, and Group C elements: any one or two of Li and Y, with a combined content of 0.00001–0.3%, further containing a combined content of 0–5%. Sb: 0~0.5%, Pb: 0–0.5%, B:0~0.5%、 Cu: 0~1.0%, Ti: 0~1.0%, Cr:0~1.0%、 Nb: 0~1.0%, Ni: 0~1.0%, Mn: 0~1.0%, Mo: 0–1.0% Ag: 0-1.0% Co: 0-1.0%, Sn: 0–1.0%, and Bi: any one or more of the following: 0% to 1.0% The remaining portion contains Zn and impurities; The coating contains an η-Zn phase or a Zn-containing phase.

2. The hot-stamped formed article according to claim 1, wherein, The chemical composition of the coating contains one or two elements from group A and group B. Group A elements: 0.0010–15% Mg, and any one or two selected from Ca or Sr, with a combined content of 0.0001% or more but less than 5.5%. Group B elements: selected from one or more of Zr, La, and Ce, with a total content of 0.0001 to 0.5%.

3. The hot-stamped formed article according to claim 1 or 2, wherein, The total amount of the elements in group C is 0.001 to 0.3%.

4. The hot-stamped formed article according to claim 2, wherein, The Mg content in group A is 1-15%.

Citation Information

Patent Citations

  • Non-contact transport device and non-contact adsorption disk

    JP2021167251A

  • Steel sheet coated with a metallic coating based on aluminum

    WO2017017513A1

  • Method for the manufacture of a hardened part which does not have LME issues

    WO2017017514A1

  • Zinc-based coating thermoforming steel based on CSP process and preparation method thereof

    CN108950160A

  • Hot-stamped article

    WO2021039971A1